2015
DOI: 10.2147/opth.s86173
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged increase in tear meniscus height by 3% diquafosol ophthalmic solution in eyes with contact lenses

Abstract: PurposeThis study aimed to evaluate the increase in tear meniscus height (TMH) induced by 3% diquafosol ophthalmic solution in eyes with contact lens (CL).MethodsTen healthy subjects wearing high-water-content CLs received topical instillation of two ophthalmic solutions – 3% diquafosol ophthalmic solution in one eye and artificial tears in the other eye. Lower TMH was measured at 5 minutes, 10 minutes, 15 minutes, 30 minutes, and 60 minutes after instillation by anterior segment optical coherence tomography.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
(19 reference statements)
1
10
0
1
Order By: Relevance
“…41 They also conducted a clinical study and found that increased tear meniscus in contact lens wearers was maintained 60 minutes after topical application of 3% diquafosol eye drops. 57 Further studies are needed to evaluate the efficacy of topical 3% diquafosol eye drops to treat CLADE.…”
Section: Recent Advances In Japanmentioning
confidence: 99%
“…41 They also conducted a clinical study and found that increased tear meniscus in contact lens wearers was maintained 60 minutes after topical application of 3% diquafosol eye drops. 57 Further studies are needed to evaluate the efficacy of topical 3% diquafosol eye drops to treat CLADE.…”
Section: Recent Advances In Japanmentioning
confidence: 99%
“…Topical administration of cyclosporine has been shown to increase tear fluid secretion, goblet cell density and decreases epithelial cell apoptosis and inflammatory cytokines in the conjunctiva and lacrimal glands, but it is clear that many patients with DED do not show a consistent therapeutic response to topical cyclosporine 11 13 . Diquafosol stimulates section of fluid and mucin from the conjunctiva directly on the ocular surface by interacting with the P2Y2 receptors to increase the tear film stability 14 . Fujihara T et al .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Diquafosol stimulates the secretion of sialic acid, which is a mucin-like substance, as well as mucin from the conjunctiva, directly onto the ocular surface. 12,13 Several studies demonstrated that diquafosol promotes tear fluid and a good safety profile with clinical improvement of the ocular surface in patients with severe DE. [13][14][15] However, some studies have reported that diquafosol may not act on the lacrimal glands directly or not provide a major improvement in symptoms related to DE.…”
mentioning
confidence: 99%